Analisis Kepailitan, Rantai Pasokan dan Tenaga Kerja di Industri Tekstil Indonesia - Rifzki Raihansah; Halimah Zahrah; Rhiza Villani; Hanifa Aulia (Teewan Journal Solutions, 2025)
The main issue in this study is the systemic impact of the bankruptcy of PT Sri Rejeki Isman Tbk (Sritex) on the national textile industry, particularly on supply chain disruptions and mass layoffs affecting thousands of workers. The purpose of this study is to analyze in depth how the bankruptcy of a large company like Sritex affects the continuity of the supply chain, the welfare of the workforce, as well as review its socio-economic implications for the textile industry in Indonesia. This research uses a descriptive qualitative approach with a literature review method. The unit of analysis in this research is relevant documents and articles regarding the Sritex bankruptcy case. Due to the nature of the literature study, no sample number of individuals was interviewed directly, but data was collected from scientific journals, economic news, and related legal documents between 2024-2025. The sampling technique used was purposive sampling based on the relevance and credibility of the sources. Data analysis was conducted using thematic synthesis techniques on the literature reviewed. The results showed that Sritex's bankruptcy caused major disruptions in the national textile supply chain, including the impact on more than ten thousand workers who were laid off. In addition, the closure of the company's operations affected the textile sector's contribution to GDP and caused extensive social impacts. Suggestions from this study are the need to strengthen corporate risk management, early warning regulations by the government, and increase labor protection through retraining and social security. Further research is recommended using a quantitative approach to measure the economic impact in more detail.